Executive function predict the quality of life and negative emotion in older adults with diabetes: A longitudinal study. Issue 4 (August 2022) - Ho, Hsiao-Ting; Lin, Sang-I.; Guo, Nai-Wen; Yang, Yi-Ching; Lin, Ming-Hsing; Wang, Chong-Shan
Abstract: Aims: To investigate the influence of executive function (EF) on current and future quality of life (QoL) and negative emotion (NE) in older adults with diabetes. Methods: A total of 128 older adults with diabetes were recruited. Independent variables (demographic information, health and medical conditions, cognitive function, life function) were collected in the first year. Dependent variables (QoL and NE) were collected for 3 years. Pearson's correlation coefficient analysis and stepwise multiple linear regression analysis were performed to identify the predictors of QoL and NE. Results: EF was the strongest predictor for overall QoL and NE in all 3 years, and accounted for 23.0–36.2% and 11.1–17.1% of the variance, respectively. The second strongest predictor for overall QoL in all 3 years was pain interference, which accounted for 3.2–5.8% of the variance. Pain interference was also the second strongest predictor for NE in the second year, accounting for 5.5% of the variance. Conclusions: The present study revealed that EF is more predictive than pain for current and future QoL and NE in older adults with diabetes. We recommend that EF be included as an indicator for diabetes surveillance, and that prevention of EF decline be a part of diabetes management plans. Highlights: EF influences QoL and NE more than pain in older adults with diabetes. EF is the strongest predictor for current and future QoL and NE. The predictive effect sizes for EF on QoL are larger than those for EF on NE. We suggest that EF be included as an indicator for diabetes surveillance. The prevention of EF decline should be included in diabetes management plans.